Augmented Gravity Model of Trade : Empirical analysis of beer exports in EU countries - Brellíková, Miriam; Sankot, Ondřej, 1988-; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis delves into the determinants of beer exports from European Union countries, examining the impact of the domestic competitive landscape (number of microbreweries) and the Covid-19 pandemic on beer export volumes. Through an Augmented Gravity Model of Trade applied to data from 2017 to 2021, we address two hypotheses regarding the influence of the domestic competitive landscape and the pandemic on the volume of beer exports. Our findings indicate a positive relationship between the number of microbreweries and beer export volumes, while the Covid-19 pandemic's impact is found to be statistically insignificant. Additionally, our analysis reveals other factors affecting beer export volumes, such as GDP per capita, distance, population, volume of beer production per capita, volume of barley production per capita, countries having common borders and importing country being an island. However, limitations in data availability and the need to broaden the scope beyond EU countries to include other major trading partners represent the scope for further research to deepen the understanding of of these determinants and their implications for the brewing industry.
Vedoucí práce: Ondřej Sankot
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses